Seabuckthorn Leaves Extract and Flavonoid Glycosides Extract from Seabuckthorn Leaves Ameliorates Adiposity, Hepatic Steatosis, Insulin Resistance, and Inflammation in Diet-Induced Obesity - Kwon, Eun-Young (Nutrients, 2017)
The aim of the current study was to elucidate the effect of seabuckthorn leaves (SL) extract and flavonoid glycosides extract from seabuckthorn leaves (SLG) on diet-induced obesity and related metabolic disturbances, and additionally, to identify whether flavonoid glycosides and other components in SL can exert a possible interaction for the prevention of metabolic diseases by comparing the effect of SL and SLG. C57BL/6J mice were fed a normal diet (ND, AIN-93G purified diet), high-fat diet (HFD, 60 kcal% fat), HFD + 1.8% (w/w) SL (SL), and HFD + 0.04% (w/w) SLG (SLG) for 12 weeks. In high fat-fed mice, SL and SLG decreased the adiposity by suppressing lipogenesis in adipose tissue, while increasing the energy expenditure. SL and SLG also improved hepatic steatosis by suppressing hepatic lipogenesis and lipid absorption, whilst also enhancing hepatic fatty acid oxidation, which may be linked to the improvement in dyslipidemia. Moreover, SL and SLG improved insulin sensitivity by suppressing the levels of plasma GIP that were modulated by secreted resistin and pro-inflammatory cytokine, and hepatic glucogenic enzyme activities. SL, especially its flavonoid glycosides (SLG), can protect against the deleterious effects of diet-induced obesity (DIO) and its metabolic complications such as adiposity, dyslipidemia, inflammation, hepatic steatosis, and insulin resistance.